Penerapan Problem Based Learning Berbantuan Kotak Perbandingan untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Putra, Komang Teguh Hendra; Suardipa, I Putu; Winangun, I Made Ari (Media Pendidikan Matematika, 2026)
This study aimed to improve the mathematics learning outcomes of sixth-grade students at SD Negeri Umeanyar on the topic of ratios through the implementation of the Problem Based Learning (PBL) model supported by ratio box media. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The subjects were 28 sixth-grade students of SD Negeri Umeanyar in the 2025/2026 academic year. Data were collected using learning outcome tests in the form of pretests and posttests administered in each cycle. The data were analyzed using quantitative descriptive analysis by comparing students’ learning outcomes in the preliminary stage, Cycle I, and Cycle II. The results showed that the implementation of the Problem Based Learning model supported by ratio box media improved students’ mathematics learning outcomes significantly. In the preliminary stage, the students’ average score was 61.25, with a learning mastery rate of 32.14%. After the action in Cycle I, the average score increased to 73.57, with learning mastery reaching 67.86%. In Cycle II, the average score increased further to 85.36, with learning mastery reaching 89.29%. This improvement occurred because students became more active in learning activities, collaborated more effectively in group discussions, and understood ratio concepts more easily through concrete media. Therefore, the PBL model supported by ratio box media is effective for improving elementary students’ mathematics learning outcomes. This finding indicates that contextual and problem-oriented learning can strengthen students’ conceptual understanding in mathematics